2018
DOI: 10.1111/psyg.12391
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive behavioural therapy can be effective in treating anxiety and depression in persons with dementia: a systematic review

Abstract: Dementia is a neurocognitive disorder that affects a person's abilities in daily functioning. Anxiety and depression symptoms are common among persons with dementia. Cognitive behavioural therapy (CBT) has been tested to manage their depression and anxiety symptoms. However, the purpose of CBT in managing these symptoms is unclear. Therefore, this paper aims to clarify whether CBT can be used to reduce depression and anxiety symptoms in persons with dementia. The electronic databases PubMed, PsycINFO, MEDLINE,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 24 publications
1
33
0
1
Order By: Relevance
“…In the context of the counsellor's expertise, the requirements for counselling programs by institutions of higher learning are important because in order for an individual to be eligible to apply as a registered counsellor, they Offering specific programs in the field of gerontological counselling is essential as Malaysia is moving towards become and advanced country. In addition, the issues faced by older people that varies from the abuse and neglect of older people with chronic illness (Abdul Aziz Jemain et al, 2001;Wan Ahmad et al, 2009;Endut & Ahmad, 2009;Bakar et al, 2009;Khadijah & Rahim 2010;Dong, 2015), dementia disease that leads to depression (Tanaka et al, 2015;Tay et al, 2018;Sharif et al, 2019), marginalized in community groups (Abdul Aziz, 2001;Manaf, 2002;Esther, Shahrul, & Low, 2006) and the accidental abuse of family members or close relatives (Jamaluddin et al, 2017) also demanded programs specific in the field of gerontology. This is also supported by the Malaysia Department of Higher Education (2011) which recommends that each HEIs offering undergraduate degree programs should consider offering a specialized program of study in line with the existing expertise and demands of current holders.…”
Section: Challenges In Terms Of Lack Of Expertisementioning
confidence: 99%
“…In the context of the counsellor's expertise, the requirements for counselling programs by institutions of higher learning are important because in order for an individual to be eligible to apply as a registered counsellor, they Offering specific programs in the field of gerontological counselling is essential as Malaysia is moving towards become and advanced country. In addition, the issues faced by older people that varies from the abuse and neglect of older people with chronic illness (Abdul Aziz Jemain et al, 2001;Wan Ahmad et al, 2009;Endut & Ahmad, 2009;Bakar et al, 2009;Khadijah & Rahim 2010;Dong, 2015), dementia disease that leads to depression (Tanaka et al, 2015;Tay et al, 2018;Sharif et al, 2019), marginalized in community groups (Abdul Aziz, 2001;Manaf, 2002;Esther, Shahrul, & Low, 2006) and the accidental abuse of family members or close relatives (Jamaluddin et al, 2017) also demanded programs specific in the field of gerontology. This is also supported by the Malaysia Department of Higher Education (2011) which recommends that each HEIs offering undergraduate degree programs should consider offering a specialized program of study in line with the existing expertise and demands of current holders.…”
Section: Challenges In Terms Of Lack Of Expertisementioning
confidence: 99%
“…Studies explicitly discussed the need to use modifications, such as simplifying the materials and shifting focus to behavioural components, to accommodate the cognitive needs of a person with dementia (Stanley et al, 2013;Tonga et al, 2016). Each person with dementia may need customised modifications based on their cognitive abilities and needs (Tay et al, 2019), and increased care-giver participation depending on the level of impairment (Spector et al, 2015). Future research should consider these modifications to develop a standardised form of CBT for people with dementia, specifically considering issues around an individual's ability to apply and generalise the strategies learned to their daily life (Losada et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, as severe cognitive deterioration tends to characterise HD's intermediate to advanced stages (e.g., [3][4][5], especially in the domains of language and executive functioning, the opportunity for effective psychological interventions may appear to be relatively limited to prodromal and early stages (e.g., 1-2). However, current evidence also shows that cognitive and behavioural techniques may be effective in treating psychological difficulties in people with moderate dementia, especially when carers are actively involved [106], and one of the uncontrolled pretestposttest studies identified by the present review showed positive short-term results for behavioural relaxation with people with advanced HD [60]. As a consequence, tailored CBT-based approaches should also be explored in the future with people with intermediate to advanced stage HD, in order to assess differences in feasibility and acceptability compared to earlier stages as well as potentially inform the development of longitudinal psychotherapeutic plans which may adapt dynamically to pwHD across the entire trajectory of the disease.…”
Section: Copingmentioning
confidence: 99%